New perspectives of renoprotection in patients with Type 2 diabetes mellitus and arterial hypertension - A. S. Ametov; T. Yu. Demidova; S. A. Kosykh (Российский кардиологический журнал)
Therapeutic effects of a new, super-selective beta blocker with NO-modulating activity, nebivolol (nebilet), on renal functional status in hypertensive patients with Type 2 diabetes mellitus were investigated. After 16 weeks of the treatment, a significant decrease in glycemia and blood pressure levels, serum atherogenity, lipid peroxidation were observed, together with increased basal NO secretion, that resulted in microalbuminuria reduction.